A CASE REPORT ON LUDWIG’S ANGINA: AN ENT EMERGENCY - MAHEEN M; ARYA GOPAKUMAR; RINCY ANNAMMA PHILIP; ZACHARIAH THOMAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Ludwig’s angina is defined as a rapidly progressive cellulitis of the floor of the mouth which involves both the submandibular and sublingual spaces of the face. The presented case was a 78-year-old female patient with a history of tooth extraction. Based on the clinical symptoms and computed tomography scan, the patient was diagnosed with Ludwig’s angina and was treated appropriately by antibiotics and steroids after emergency tracheostomy and airway management. Early diagnosis and proper management can limit the morbidity and mortality rate of Ludwig’s angina